Moderating Role of Personality in Interactional Justice, and Counterproductive Work Behavior in Police Officers" - Maqsood, Amna; Qayyum, Dr Shazia; Tariq, Dr Shahnila (The journal of contemporary issues in business and government, 2021)
This research aims to investigate relationship in Interactional Justice, Personality and Counterproductive Work Behavior. It was hypothesized that an association would exist among Interactional Justice (Interpersonal and Informational Justice), Personality (Extraversion, Conscientiousness, Agreeableness, Neuroticism and Openness to Experience) and Counterproductive Work Behavior. The sample consisted of police officers (n=209) selected from Lahore using non-probability purposive sampling technique. In addition to demographic information sheet, Organizational Justice Measure (Colquitt, 2001), The Big Five Inventory (BFI-10) (Rammstedt & John, 2007) and Counterproductive Work Behavior Checklist (Spector, 2006) were used to assess the relationship. The data were analyzed using Pearson Product Moment correlation and hierarchal multiple regression analysis using SPSS version 20. The present study indicated that Interactional Justice i.e., (Interpersonal & Informational Justice) had a negative correlation with Counterproductive Work Behavior. Extraversion and Neuroticism had positive while Conscientiousness, Agreeableness and Openness to Experience had a negative correlation with Counterproductive Work Behavior. Moreover, according to moderation analysis Personality trait i.e., Conscientiousness acts as a moderator with Interactional Justice (i.e., Interpersonal and Informational Justice) for Counterproductive Work Behavior. This study would be helpful and beneficial in the field of organizational psychology and in all industrial fields, in understanding the concern of employees regarding Interactional Justice (Interpersonal & Informational Justice), Personality Traits (Extraversion, Conscientiousness, Agreeableness, Neuroticism and Openness to Experience) and Counterproductive Work Behavior which would otherwise increase the employee’s determination and ultimately benefit the organization.